The effect of a company's innovation orientation culture on employee turnover among selected non-governmental organizations in Samburu, Kenya - Julius Lentawa (Ümit Hacıoğlu, 2021)
This paper examines the effect of a company's innovation orientation culture on employee turnover among selected non-governmental organizations in Samburu, Kenya. A stratified random sampling technique was used to select 78 NGOs operating in Samburu County for the analysis, the study population comprised 11 senior management teams, 14 technical teams and 78 junior staff in 24 selected and active NGOs in Samburu. The analysis gathered both qualitative and quantitative data. A structured questionnaire was used to collect quantitative data and an interview guide was used to collect qualitative data. Thematic data analysis was used to interpret qualitative data, which included common terms, phrases, themes, and patterns. Quantitative data were analyzed using descriptive statistics which includes frequencies, means, and standard deviation. Findings Results showed that innovation orientation is positively correlated with employee turnover (r=0.375, P=0.01). This supports Chow et al’s (2001) study which revealed that innovation orientation as part of an organization's culture has a significant effect on employee turnover. This study also discovered that an innovation orientation culture embedded in an NGO's ideology will help to reduce turnover because workers feel valued when their work is recognized for creativity and innovation.